Students’ Perceptions in Using Zoom Video Conference as a Learning Media - Alfitriani Siregar; Resty Wahyuni; Putri Ramadani Hutabarat (Departement of Mathematics Education, 2023)
This research aimed to determine students' perceptions toward using zoom as a learning medium during online EFL (English as a foreign Language) learning. This research also uses a qualitative descriptive method. Data sources were obtained from 50 of 8th-semester students by distributing questionnaires, and ten randomly selected students for interviews. The results of the questionnaire obtained were processed using quantitative and interviews by entering interview transcripts. The results of this study indicate that students have positive perceptions and attitudes about using zoom as a learning medium during online EFL learning. Students who consider zoom, a video conferencing technology that assists students with online learning and does not restrict discussion in English, can also utilize zoom to improve and enhance their English. Zoom allows us to have a virtual classroom and it is the ideal choice for learning, discussing, and attending meetings and webinars since its functions allow students to communicate with both the instructor and their peers at the same time, anywhere as learning media.